Identificación del parasito "Neospora caninum" en bovinos por medio del método de ELISA, en las haciendas ganaderas del cantón Tulcán en la Provincia del Carchi - Cruz Montenegro, Marco Xavier (2011)
Canine Neosporosis in milking cows is considered a serious problem to animal health in dairy cattle. It causes abortion and embryo reabsorption in the first third of gestation. It is a cosmopolitan disease detected in the eighties. The present research work wants to contribute to the diagnoses of bovine Neosporosis in the Carchi province, an important milking zone of Ecuador. The work was done in 23 milking cattle ranches (10 percent of the total Carchi population) sampling 180 cows on blood serum. The diagnosis was made in LIVEXLAB of Ecuador, using ELISA method. The research findings showed 51.64 percent positive serum samples and 48.35 negatives out of 180 examined samples. All 23 milking cattle ranches examined had positive animals. The sampled cows were chosen randomly without consideration of age, race an with and without childbirth stories.